Methodological problems of land use environmental impact assessment as a planned economic activity - Tretyak, А; Klimova, І (Land Management, Cadastre and Land Monitoring, 2019)
Assessment of the environmental impact of land use as a planned economic activity related to a number of issues, in particular theoretical and methodological character. One of the main problems in the development of such a theory is to built its basis, the starting point for the development of which is to determine the methodological procedure.Despite the large amount of literature devoted to the study of various aspects of environmental impact assessment, it is necessary to state that no sustainable, complete definition of this concept has been formed in the environmental literature.The purpose of the article is to review and compile directions and approaches formed by certain criteria in the doctrine of environmental legislation to define the concept of environmental impact assessment of land use as a planned economic activity, to cover their heterogeneous and general nature for developing a holistic view of ways of understanding this concept, as well as an account of one's own vision of the optimal methodological basis for defining the concept of environmental impact assessment of land use.From the example of foreign experience it is established that in the modern period the following procedures are widely recognized: previous environmental impact assessment - screening; definition of environmental assessment tasks - scoping; generalization, comparison and choice of alternatives.From the authors' point of view, it is proposed to supplement the environmental impact assessment with the following steps as well: assessment of environmental parameters; mitigation; decision making.Based on the analysis of the considered methodologies for environmental situation assessment, we propose a methodology for geoinformation land-ecological-techno-geochemical modeling of environmental situations, based on the use of GIS technologies for graphical overlay of evaluation maps.This methodology is the optimal basis for determining the environmental impact assessment of land use as a planned economic activity, both in the early stages of environmental impact assessment and when comparing alternatives.Keywords: concept of environmental impact assessment of land use as a planned economic activity; evaluation procedures; planned business activities, "screening"; "scoping"; “generalization”; “Methodology of geoinformation land-ecological-techno-geochemical modeling”; GIS technologies.